2023
DOI: 10.3390/ph16030367
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Novel Hydroxamic Acid-Based Organoselenium Hybrids

Abstract: We report the design and synthesis of novel hydroxamic acid-tethered organoselenium (OSe) hybrids. Their antimicrobial and anticancer activities were assessed against different microbes (e.g., Candida albicans (C. albicans), Escherichia coli (E. coli), and Staphylococcus aureus (S. aureus)), as well as liver and breast carcinomas. OSe hybrid 8 showed promising anticancer activity, with IC50 = 7.57 ± 0.5 µM against HepG2 and IC50 = 9.86 ± 0.7 µM against MCF-7 cells. Additionally, OSe compounds 8 and 15 exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“… 16 , 17 Sulfur, selenium, and tellurium-containing compounds have been important subjects of investigation due to their expressive number of pharmacological properties. 18 , 19 Among them, antimicrobial, 20 anticancer cell proliferation, 21 , 22 anti-HIV, 23 anti-Alzheimer’s, 24 and potential infection control by SARS-CoV-2 can be highlighted. 25 In this context, we would like to highlight the research developed by Gritzenco et al 26 where the authors obtained encouraging results regarding the alkynyl selenide compounds as a potential anticancer agent ( Figure 1 b) and the recent successful examples of selenium molecules against breast cancer ( Figure 1 c).…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 Sulfur, selenium, and tellurium-containing compounds have been important subjects of investigation due to their expressive number of pharmacological properties. 18 , 19 Among them, antimicrobial, 20 anticancer cell proliferation, 21 , 22 anti-HIV, 23 anti-Alzheimer’s, 24 and potential infection control by SARS-CoV-2 can be highlighted. 25 In this context, we would like to highlight the research developed by Gritzenco et al 26 where the authors obtained encouraging results regarding the alkynyl selenide compounds as a potential anticancer agent ( Figure 1 b) and the recent successful examples of selenium molecules against breast cancer ( Figure 1 c).…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Hence, OSe hybrids are considered privileged scaffolds in drug discovery for cancer treatment. 18,[30][31][32][33][34] Recently, we reported the OSe-containing isomaleimide V with good antioxidant, cytoprotective, and antiapoptotic activity against oligodendrocytes. 17,19,35 Additionally, the OSe-bearing Nsuccinimide VI, synthesized in our laboratory, exhibited good anticancer activity against HEPG2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…A recent high-throughput screening study by Jin et al [18,21] identified ebselen as a promising antiviral agent among more than 10,000 candidates as a lead inhibitor of M pro [18,22]. Within this context, the antiviral activity of ebselen suggested the promise of OSe agents as possible M pro inhibitors by interaction with the virus infection cycle [23,24]. Ebselen can efficiently bind to the cysteine located in the M pro active site, thus forming selenosulfide, which causes the inactivation of the virus with an IC 50 = 0.67 µM [22,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, the antiviral activity of ebselen suggested the promise of OSe agents as possible M pro inhibitors by interaction with the virus infection cycle [23,24]. Ebselen can efficiently bind to the cysteine located in the M pro active site, thus forming selenosulfide, which causes the inactivation of the virus with an IC 50 = 0.67 µM [22,23,25].…”
Section: Introductionmentioning
confidence: 99%